2008
DOI: 10.1027/0269-8803.22.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Does Autonomic Arousal Distinguish Good and Bad Decisions?

Abstract: The Somatic Marker Hypothesis (SMH) proposes that physiological feedback to the brain influences cognitive appraisal and decision-making; however, the strength of evidence in support of the SMH is equivocal. In this study we examined the validity of the SMH by measuring physiological arousal in a population of healthy individuals playing the Iowa Gambling Task (IGT); a computerised card game designed to assess real-life decisionmaking. We also aimed to clarify uncertainty regarding the influence of reinforcer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
(162 reference statements)
2
23
0
1
Order By: Relevance
“…However, the fact that impaired and unimpaired task performance cannot be physiologically distinguished suggests that SMs do not discriminate between good and bad decision makers, in terms of overall performance or long-term consequences, but instead reflect only immediate decisions. According to Jenkinson et al (2008), the pattern of autonomic activity found in their study is consistent with the suggestion of Tomb, Hauser, Deldin, and Caramazza (2002) that the overall performance on the IGT is independent of somatic activity, which instead only reflects the magnitude of immediate reward or punishment. The differentiation between good and bad decision making ("good" and "bad" decks) and good and bad decision makers (impaired vs. nonimpaired performance) may provide some explanations for the conflicting evidence with respect to the SM hypothesis.…”
Section: Eda and Decision Makingsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the fact that impaired and unimpaired task performance cannot be physiologically distinguished suggests that SMs do not discriminate between good and bad decision makers, in terms of overall performance or long-term consequences, but instead reflect only immediate decisions. According to Jenkinson et al (2008), the pattern of autonomic activity found in their study is consistent with the suggestion of Tomb, Hauser, Deldin, and Caramazza (2002) that the overall performance on the IGT is independent of somatic activity, which instead only reflects the magnitude of immediate reward or punishment. The differentiation between good and bad decision making ("good" and "bad" decks) and good and bad decision makers (impaired vs. nonimpaired performance) may provide some explanations for the conflicting evidence with respect to the SM hypothesis.…”
Section: Eda and Decision Makingsupporting
confidence: 85%
“…To clarify the extent to which SMs guide decisions, Jenkinson, Baker, Edelstyn, and Ellis (2008) investigated if SC measures distinguish between good and bad decision makers. Forty-one healthy participants (30 females, 11 males) performed a computerized version of the IGT with either play money or real money as reinforcers.…”
Section: Eda and Decision Makingmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in certain situations, arousal has been found to impact ad evaluations, whereas valence has not (Gorn, Tuan Pham, & Yatming Sin, 2001). Similarly, arousal has been found to help discriminate between good and bad decks in the Iowa Gambling Task, but not between good and bad decision making in general (Jenkinson, Baker, Edelstyn, & Ellis, 2008).…”
Section: Types Of Emotions 20mentioning
confidence: 99%